The effect of eversion and conventional-patch technique in carotid surgery on postoperative hypertension - Demirel, Serdar; Bruijnen, Hans; Attigah, Nicolas; Hakimi, Maani; Böckler, Dittmar (Journal of vascular surgery, 2011)
Objective - Postcarotid endarterectomy hypertension (HTN) is associated with neurological and cardiac complications. The purpose of this study was to assess the influence of eversion carotid endarterectomy (E-CEA) and conventional carotid endarterectomy (C-CEA) on postoperative blood pressure in the first 4 days after surgery. - Methods - Two hundred seventy-six consecutive CEAs that were performed between February 2008 and September 2009 were reviewed retrospectively with a computerized registry. After exclusion of patients with severe stroke (modified Rankin Scale of 3-5), prior contralateral and ipsilateral carotid surgery and more than 70% stenosis of the contralateral carotid artery, 201 cases remained (E-CEA group: n = 100 vs C-CEA group: n = 101) for analysis. Results in terms of systolic blood pressure, use of intravenous and oral vasodilators, alterations of the existing antihypertensive medications, and perioperative complications (neck hematoma, myocardial infarction, stroke, and death) were compared. - Results - Groups were similar with regard to age, sex, and cardiovascular risk factors except for a higher incidence of nicotine use (59% vs 43%; P = .02) in the C-CEA group. Patients in the C-CEA group had a significantly higher percentage of symptomatic carotid artery stenosis (54% vs 23%, respectively; P < .0001). Despite a lower preoperative (baseline) mean systolic blood pressure (130 mm Hg vs 135 mm Hg; P = .02) patients in the E-CEA group had a significantly higher mean systolic blood pressure in the postoperative course up to the day 4 after surgery (134 mm Hg vs 126 mm Hg; P < .0001) and required more frequent intravenous (28% vs 9.9%; P = .001) and oral vasodilators (54% vs 27.7%; P = .0002) compared to those in the C-CEA group. Two-thirds (14 of 21 = 66%) of patients in the E-CEA group with preoperative high blood pressure (systolic blood pressure ≥140 mm Hg and diastolic pressure ≥90 mm Hg) required vasodilators and only one-third (11 of 33 = 33%) in the C-CEA group (P = .03). Atropine use due to bradycardia was necessary after 8 cases (8%) in the C-CEA group and only after 1 case (1%) in the E-CEA group (P = .03). Furthermore, the dosage of existing antihypertensive medications was increased and/or additional medications were prescribed twofold more in the E-CEA group (33% vs 17%; P = .009). No statistically significant difference was noted in the perioperative complication rate. - Conclusion - It is concluded that E-CEA is associated with significantly higher postoperative blood pressure that persists for at least 4 days after surgery. Patients with inadequate preoperative high blood pressure control are particularly at risk after E-CEA.